Water-based binder, preparation method and application
By using an aqueous binder composed of specific monomers and preparing using a precipitation polymerization process, the shortcomings of the negative electrode binder of existing lithium-ion batteries in high-temperature circulation and processing performance are solved, and the excellent cycle life and low-temperature performance of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202411777487.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The negative electrode adhesives of existing lithium-ion batteries have shortcomings in high-temperature circulation and processing performance, resulting in capacity loss and difficulty in processing the pole sheet.
An aqueous binder is used, which consists of ethylenically unsaturated carboxylic acid, ethylenically unsaturated nitrile monomer, carboxyl group-free ethylenically unsaturated hydrophilic monomer, ethylenically unsaturated hydrophobic monomer and crosslinked monomer. It is prepared by a precipitation polymerization process and has excellent dispersion, adhesion and flexibility.
This water-based binder significantly improves the high-temperature storage and high-temperature circulation performance of lithium-ion batteries, and improves the processing performance of the pole sheet, ensuring the excellent cycle life and low-temperature performance of the battery.
Smart Images

Figure BDA0005171863700000041 
Figure BDA0005171863700000042 
Figure BDA0005171863700000051
Abstract
Description
Technical Field
[0001] The invention relates to a lithium ion battery material and a preparation method thereof, in particular to a lithium ion secondary battery negative electrode binder, a preparation method thereof and application thereof. Background Art
[0002] Lithium-ion batteries are considered to be the most promising mobile energy storage technology due to their high energy density, long cycle life, and environmental friendliness, and are widely used in electronic products, electric vehicles, energy storage equipment, and other fields.
[0003] Lithium-ion batteries are mainly composed of pole pieces (including positive and negative electrodes), electrolytes and separators; pole pieces are generally composed of active materials, conductive agents, dispersants, binders and current collectors; in the process of preparing pole pieces, the electrode active materials, conductive agents, dispersants and binder solutions are usually mixed and homogenized and then applied to the current collector, and then dried, calendered and other processes are performed to form a complete pole piece. In this process, the binder mainly plays a bonding role to maintain the integrity of the pole piece.
[0004] At present, the most widely used negative electrode binder is styrene-butadiene rubber solution (SBR), which needs to be added with carboxymethyl cellulose (CMC) as a thickener and dispersant during use. However, CMC has average viscosity, high brittleness and poor flexibility, and the electrode is prone to cracking during charge and discharge. At the same time, when SBR is used as a binder based on the point-point bonding mechanism for graphite negative electrodes and silicon-based new negative electrodes, the point bonding is very easy to lose its adhesion due to the repeated expansion and contraction of the volume of the graphite negative electrode and the silicon-based negative electrode during the charge and discharge cycle, resulting in capacity loss, especially high-temperature storage and high-temperature cycle performance degradation. In addition, SBR has a large swelling degree in the electrolyte (50% to 200%), which increases the spacing between the negative electrode active materials. At the same time, the large swelling of the electrolyte will cause the adhesion of the binder to the copper foil or the active material to decrease, causing the battery performance to deteriorate.
[0005] In the prior art, PAA is used as a binder, which has high bonding strength, low electrolyte swelling, and excellent high-temperature cycle performance. However, the polymer has a high glass transition temperature, which can easily lead to hard and brittle problems on the pole piece after coating. Therefore, the binder is prone to cracking during the coating process, many stripes after cold pressing, decarbonization of the edges during cutting, and powder loss at the bend of the pole piece during winding. The processing performance is poor, which seriously restricts its application in batteries.
[0006] CN111139002B discloses a water-soluble adhesive for lithium-ion batteries, which adopts a ternary copolymer of acrylonitrile, 2-acrylamide-2-phenylethanesulfonic acid and methacrylic acid. The molecular chain characteristics of the water-soluble polymer give it a surface-to-surface bonding mechanism, forming a network bond inside the pole piece, enhancing the bonding force between active materials and between active materials and substrates. At the same time, it has good dispersion performance and slurry stability, as well as lower electrolyte swelling characteristics. Compared with SBR latex, it can significantly improve the high-temperature storage and high-temperature cycle performance of lithium-ion batteries, but the processing performance of the pole piece needs to be further improved.
[0007] CN115312779A designs the raw materials and contents of polymer solution A and polymer solution B to prepare an aqueous polymer binder with a three-dimensional cross-linked structure. The aqueous polymer binder has good flexibility and high bonding strength and can be used to prepare negative electrode plates for lithium-ion batteries. However, the efficiency of preparing the binder needs to be improved.
[0008] Therefore, in view of the current SBR dispersion performance and high-temperature cycle performance and PAA electrode processing problems, providing a binder product with better dispersibility, higher adhesion and better flexibility has become a technical problem that needs to be solved urgently. Summary of the invention
[0009] The object of the present invention is to provide a water-based binder and a preparation method and application thereof. Compared with SBR, the binder has good bonding performance and lower dissolution, which can ensure that the lithium-ion battery has an excellent cycle life. At the same time, compared with the existing PAA products, it shows better flexibility, which can ensure that the lithium-ion battery pole piece has excellent processing performance.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] In one aspect, the present invention provides an aqueous binder obtained by polymerizing a raw material comprising the following components:
[0012] a) 20 wt% to 45 wt% of at least one of an ethylenically unsaturated carboxylic acid or an ethylenically unsaturated carboxylic anhydride;
[0013] b) 20 wt% to 45 wt% of an ethylenically unsaturated nitrile monomer;
[0014] c) 5 wt% to 30 wt% of an ethylenically unsaturated hydrophilic monomer not containing a carboxyl group;
[0015] d) 10 wt% to 40 wt% of ethylenically unsaturated hydrophobic monomers;
[0016] e) 0.15 wt% to 1 wt% of a cross-linking monomer.
[0017] In the present invention, among the ethylenically unsaturated carboxylic acid and the ethylenically unsaturated carboxylic acid anhydride, the ethylenically unsaturated carboxylic acid is preferred, and at least one of acrylic acid and methacrylic acid is more preferred.
[0018] In the present invention, the ethylenically unsaturated nitrile monomer is selected from at least one of acrylonitrile, α-haloacrylonitrile, and α-alkylacrylonitrile, preferably at least one of acrylonitrile, α-chloroacrylonitrile, α-bromoacrylonitrile, methacrylonitrile, and ethacrylonitrile.
[0019] In the present invention, the ethylenically unsaturated hydrophilic monomer not containing a carboxyl group is at least one of acrylamide, methacrylamide, hydroxyethyl acrylate, ethoxyethoxyethyl acrylate, hydroxyethyl methacrylate, sodium vinyl sulfonate, and sodium p-styrene sulfonate.
[0020] In the present invention, the ethylenically unsaturated hydrophobic monomer is at least one of styrene, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, hexyl acrylate, hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, decyl acrylate, decyl methacrylate, glycidyl acrylate, and glycidyl methacrylate.
[0021] In the present invention, the crosslinking monomer is at least one of diacetone acrylamide, ethyl acetoethoxy methacrylate, divinylbenzene, ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,6-hexanediol diacrylate, allyl methacrylate, and pentaerythritol triallyl ether.
[0022] On the other hand, the present invention also provides a method for preparing an aqueous binder, comprising the following steps:
[0023] Step 1: placing an aqueous solution of protective glue in a reactor and heating it;
[0024] Step 2: Add the four monomers (a), (b), (c), (e) and an initiator into a reaction kettle to initiate a polymerization reaction;
[0025] Step 3: After the polymerization is completed and the temperature is kept high, a neutralizing agent is added to adjust the pH to obtain a polymer solution A;
[0026] Step 4: adding the emulsifier, (a), (d), (e) and the initiator into the reactor of step 3 simultaneously to further initiate the polymerization reaction;
[0027] Step 5: After the polymerization is completed and the temperature is kept high, a neutralizing agent is added to adjust the pH to obtain a water-based adhesive.
[0028] In the present invention, the protective colloid in step 1 is selected from polyvinyl alcohol and / or sodium carboxymethyl cellulose; and / or the amount of the protective colloid is 0.1-1wt%, preferably 0.3-0.8wt% of the total amount of the five monomers (a), (b), (c), (d) and (e).
[0029] In the present invention, the temperature of the heating in step 1 is 30-85°C, preferably 35-80°C.
[0030] In the present invention, the initiator in step 2 comprises an oxidant and a reducing agent, and the mass ratio of the oxidant to the reducing agent is 1:2-2:1, preferably 1:1-2:1.
[0031] In the present invention, the oxidant is selected from at least one of ammonium persulfate, sodium persulfate, potassium persulfate, tert-butyl hydroperoxide and hydrogen peroxide, preferably sodium persulfate; the reducing agent is selected from at least one of sodium hydrosulfite, isoascorbic acid, sodium pyrosulfite and sodium bisulfite, preferably sodium bisulfite; and / or, the amount of the oxidant is 0.1-1wt% of the total amount of the five monomers (a), (b), (c), (d) and (e), preferably 0.2-0.8wt%; the amount of the reducing agent is 0.1-1wt% of the total amount of the five monomers (a), (b), (c), (d) and (e), preferably 0.2-0.8wt%.
[0032] In the present invention, the amounts of monomers (a) and (e) in step 2 account for 75%-98% and 3%-40% of the total amount, respectively.
[0033] In the present invention, the polymerization reaction temperature in step 2 is 30-85° C., preferably 35-80° C.; the reaction time is 3-6 h, preferably 4-5 h.
[0034] In the present invention, the insulation time in step 3 is 1-3 hours, preferably 1.5-2 hours.
[0035] In the present invention, the neutralizing agent in step 3 is selected from one or more aqueous solutions of NaOH, Na2CO3, LiOH, and lithium carbonate, and the pH after adjustment is 5.5-7.5.
[0036] In the present invention, the emulsifier in step 4 is selected from one or more of sodium allyl alkyl succinate sulfonate, methacrylate polyether phosphate, alkyl alcohol ether sulfate containing allyl group, alkyl alcohol ether sulfate containing double bond, dialkyl sulfosuccinate containing double bond, alkyl propylene phenoxy polyether sulfate, polyether ammonium phosphate containing double bond, polyphenyl ring polyoxyethylene ether sulfate or sulfonate, fatty alcohol polyoxyethylene ether sulfate; and / or, the amount of the emulsifier is 0.05-0.5wt%, preferably 0.1-0.3wt% of the total amount of the five monomers (a), (b), (c), (d), and (e).
[0037] In the present invention, the initiator in step 4 is selected from at least one of ammonium persulfate, sodium persulfate, potassium persulfate, tert-butyl hydroperoxide and hydrogen peroxide, and the amount of the initiator is 0.05-0.5wt%, preferably 0.1-0.3wt% of the total amount of the five monomers (a), (b), (c), (d) and (e).
[0038] In the present invention, the amounts of monomers (a) and (e) in step 4 account for 2%-25% and 60%-97% of the total amount, respectively.
[0039] In the present invention, the reaction temperature in step 4 is 70-90°C, preferably 75-85°C; the reaction time is 3-6h, preferably 4-5h.
[0040] In the present invention, the insulation time in step five is 1-3h, preferably 1.5-2h; and / or, the neutralizing agent in step five is selected from one or more aqueous solutions of NaOH, Na2CO3, LiOH, and lithium carbonate, and the adjusted pH is 6-8.
[0041] In the present invention, the solid content of the aqueous binder is 4-10wt%, preferably 5-8wt%.
[0042] Finally, the present invention provides the use of the aqueous binder as a binder for negative electrode active materials, wherein the negative electrode material is selected from artificial graphite, natural graphite, hard carbon, and silicon carbon.
[0043] The present invention has the following beneficial effects:
[0044] (1) The aqueous binder of the present invention first adopts the precipitation polymerization process to prepare a polymer that not only has excellent dispersibility and adhesion, but also exhibits excellent low dissolution characteristics in the electrolyte DMC. This macromolecule is used as an emulsifier for the second step polymerization, which can provide excellent polymerization stability and control the dissolution performance of the entire polymer, thereby giving the battery excellent cycle performance.
[0045] (2) The aqueous binder prepared by the two-step polymerization process of the present invention has good toughness and gives the pole piece excellent processing performance
[0046] (3) The water-based binder polymer molecular chain of the present invention contains functional groups such as cyano, hydroxyl, amide, and ester groups, which promote the conduction of lithium ions, reduce the internal resistance of lithium batteries, and improve the low-temperature performance of lithium batteries. DETAILED DESCRIPTION
[0047] The present invention will be further described below through specific embodiments. The specific embodiments are only detailed descriptions of the contents of the present invention, but not limiting the scope of the present invention.
[0048] Table 1 Raw materials and sources:
[0049]
[0050]
[0051] The main raw materials and proportions used in the embodiments and comparative examples are shown in Table 1:
[0052] Table 2 Main raw materials and proportions for preparing water-based binders
[0053]
[0054]
[0055] Example 1
[0056] (1) Add 1 g PVA2488 and 500 g deionized water into a reactor, start stirring and heat to 50°C;
[0057] (2) 20 g of acrylic acid, 20 g of acrylonitrile, 10 g of acrylamide, and 0.05 g of 1,3-butanediol dimethacrylate were mixed;
[0058] (3) 0.8 g of APS was dissolved in 50 g of water and 0.8 g of NaHSO3 was dissolved in 50 g of water to prepare an oxygen-reduction initiator solution;
[0059] (4) simultaneously adding the mixed monomers in step (2) and the aqueous initiator solution in step (3) to the reactor in step (1), the reaction temperature is 35° C., the adding time is 3 h, after the adding is completed, the temperature is raised to 80° C. and kept for 2 h, and a 10% aqueous sodium hydroxide solution is added to adjust the solution pH to 6.0;
[0060] (5) 0.5 g (active ingredient) NRS-1230 emulsifier, 12.5 g water, 5 g acrylic acid, 14 g styrene, 30 g butyl acrylate, and 0.95 g 1,3-butanediol dimethacrylate were added to a pre-emulsification tank.
[0061] (6) Dissolve 0.25 g of APS in 50 g of water to prepare an initiator solution;
[0062] (7) simultaneously adding the mixed monomers in step (5) and the initiator aqueous solution in step (6) to the reaction kettle in step (1) for 3 hours and keeping warm for 2 hours. After the reaction is completed, add 10% sodium hydroxide aqueous solution to adjust the pH value of the solution to 7.5;
[0063] Example 2
[0064] (1) Add 0.5 g PVA2488 and 500 g deionized water into a reactor, start stirring and heat to 50°C;
[0065] (2) 20 g of acrylic acid, 40 g of acrylonitrile, 25 g of acrylamide, and 0.17 g of 1,3-butanediol dimethacrylate were mixed;
[0066] (3) 0.35 g of APS was dissolved in 50 g of water, and 0.35 g of NaHSO3 was dissolved in 50 g of water to prepare an oxygen-reduction initiator solution;
[0067] (4) simultaneously adding the mixed monomers in step (2) and the aqueous initiator solution in step (3) to the reactor in step (1), the reaction temperature is 50° C., the adding time is 3 h, after the adding is completed, the temperature is raised to 70° C. and kept for 2 h, and a 10% aqueous sodium hydroxide solution is added to adjust the pH of the solution to 6.0;
[0068] (5) Add 0.075 g (active ingredient) NRS-1230 emulsifier, 4 g water, 1 g acrylic acid, 3.5 g styrene, 10 g butyl acrylate, and 0.33 g 1,3-butanediol dimethacrylate into a pre-emulsification tank.
[0069] (6) Dissolve 0.075 g of APS in 50 g of water to prepare an initiator solution;
[0070] (7) simultaneously adding the mixed monomers in step (5) and the initiator aqueous solution in step (6) to the reaction kettle in step (1) for 3 hours and keeping warm for 2 hours. After the reaction is completed, add 10% sodium hydroxide aqueous solution to adjust the pH value of the solution to 7.5;
[0071] Example 3
[0072] (1) Add 0.1 g PVA2488 and 500 g deionized water into a reactor, start stirring and heat to 50°C;
[0073] (2) 25 g of acrylic acid, 30 g of acrylonitrile, 15 g of acrylamide, and 0.14 g of 1,3-butanediol dimethacrylate were mixed;
[0074] (3) Dissolve 0.1 g of APS in 50 g of water and 0.1 g of NaHSO3 in 50 g of water to prepare an oxygen-reduction initiator solution;
[0075] (4) simultaneously adding the mixed monomers in step (2) and the aqueous initiator solution in step (3) to the reactor in step (1), the reaction temperature is 80° C., the adding time is 3 h, after the adding is completed, the temperature is raised to 90° C. and kept for 2 h, and a 10% aqueous sodium hydroxide solution is added to adjust the solution pH to 6.0;
[0076] (5) 0.15 g (active ingredient) NRS-1230 emulsifier, 8 g water, 5 g acrylic acid, 6.5 g styrene, 18 g butyl acrylate, and 0.36 g 1,3-butanediol dimethacrylate were added to a pre-emulsification tank.
[0077] (6) Dissolve 0.15 g of APS in 50 g of water to prepare an initiator solution;
[0078] (7) simultaneously adding the mixed monomers in step (5) and the initiator aqueous solution in step (6) to the reaction kettle in step (1) for 3 hours and keeping warm for 2 hours. After the reaction is completed, add 10% sodium hydroxide aqueous solution to adjust the pH value of the solution to 7.5;
[0079] Example 4
[0080] (1) Add 0.5 g PVA2488 and 500 g deionized water into a reactor, start stirring and heat to 50°C;
[0081] (2) 40 g of acrylic acid, 35 g of acrylonitrile, 10 g of acrylamide, and 0.17 g of allyl methacrylate were mixed;
[0082] (3) 0.35 g of APS was dissolved in 50 g of water, and 0.35 g of NaHSO3 was dissolved in 50 g of water to prepare an oxygen-reduction initiator solution;
[0083] (4) simultaneously adding the mixed monomer in step (2) and the aqueous initiator solution in step (3) to the reaction kettle in step (1), heating to 50° C., adding for 3 h, heating to 80° C. and keeping warm for 2 h after the addition is complete, and adding 10% aqueous sodium hydroxide solution to adjust the pH of the solution to 6.0;
[0084] (5) 0.15 g (active ingredient) NRS-1230 emulsifier, 4 g water, 1 g acrylic acid, 3.5 g styrene, 10 g isooctyl acrylate, and 0.33 g allyl methacrylate were added to a pre-emulsification tank.
[0085] (6) Dissolve 0.075 g of APS in 50 g of water to prepare an initiator solution;
[0086] (7) simultaneously adding the mixed monomers in step (5) and the initiator aqueous solution in step (6) to the reaction kettle in step (1) for 3 hours and keeping warm for 2 hours. After the reaction is completed, add 10% sodium hydroxide aqueous solution to adjust the pH value of the solution to 7.5;
[0087] Example 5
[0088] (1) Add 0.5 g PVA2488 and 500 g deionized water into a reactor, start stirring and heat to 50°C;
[0089] (2) 25 g of acrylic acid, 30 g of acrylonitrile, 15 g of acrylamide, and 0.14 g of pentaerythritol triallyl ether were mixed;
[0090] (3) 0.35 g of APS was dissolved in 50 g of water, and 0.35 g of NaHSO3 was dissolved in 50 g of water to prepare an oxygen-reduction initiator solution;
[0091] (4) simultaneously adding the mixed monomer in step (2) and the aqueous initiator solution in step (3) to the reaction kettle in step (1), heating to 50° C., adding for 3 h, heating to 80° C. and keeping warm for 2 h after the addition is complete, and adding 10% aqueous sodium hydroxide solution to adjust the pH of the solution to 6.0;
[0092] (5) 0.15 g (active ingredient) NRS-1230 emulsifier, 4 g water, 5 g acrylic acid, 6.5 g styrene, 18 g isooctyl acrylate, and 0.36 g pentaerythritol triallyl ether were added to a pre-emulsification tank.
[0093] (6) Dissolve 0.15 g of APS in 50 g of water to prepare an initiator solution;
[0094] (7) simultaneously adding the mixed monomers in step (5) and the initiator aqueous solution in step (6) to the reaction kettle in step (1) for 3 hours and keeping warm for 2 hours. After the reaction is completed, add 10% sodium hydroxide aqueous solution to adjust the pH value of the solution to 7.5;
[0095] Example 6
[0096] (1) Add 0.5 g CMC and 500 g deionized water into a reactor, start stirring and heat to 50 °C;
[0097] (2) 35 g of acrylic acid, 30 g of acrylonitrile, 5 g of acrylamide, and 0.05 g of pentaerythritol triallyl ether were mixed;
[0098] (3) 0.35 g of APS was dissolved in 50 g of water, and 0.35 g of NaHSO3 was dissolved in 50 g of water to prepare an oxygen-reduction initiator solution;
[0099] (4) simultaneously adding the mixed monomer in step (2) and the aqueous initiator solution in step (3) to the reaction kettle in step (1), heating to 50° C., adding for 3 h, heating to 80° C. and keeping warm for 2 h after the addition is complete, and adding 10% aqueous sodium hydroxide solution to adjust the pH of the solution to 6.0;
[0100] (5) 0.15 g (active ingredient) NRS-1230 emulsifier, 4 g water, 5 g acrylic acid, 6.85 g styrene, 18 g isooctyl acrylate, and 0.1 g pentaerythritol triallyl ether were added to a pre-emulsification tank.
[0101] (6) Dissolve 0.15 g of APS in 50 g of water to prepare an initiator solution;
[0102] (7) simultaneously adding the mixed monomers in step (5) and the initiator aqueous solution in step (6) to the reaction kettle in step (1) for 3 hours and keeping warm for 2 hours. After the reaction is completed, add 10% sodium hydroxide aqueous solution to adjust the pH value of the solution to 7.5;
[0103] Comparative Example 1:
[0104] (1) Add 0.5 g PVA2488 and 500 g deionized water into a reactor, start stirring and heat to 50°C;
[0105] (2) Mix 40 g of acrylic acid, 35 g of acrylonitrile, and 10 g of acrylamide;
[0106] (3) 0.35 g of APS was dissolved in 50 g of water, and 0.35 g of NaHSO3 was dissolved in 50 g of water to prepare an oxygen-reduction initiator solution;
[0107] (4) simultaneously adding the mixed monomer in step (2) and the aqueous initiator solution in step (3) to the reaction kettle in step (1), heating to 50° C., adding for 3 h, heating to 80° C. and keeping warm for 2 h after the addition is complete, and adding 10% aqueous sodium hydroxide solution to adjust the pH of the solution to 6.0;
[0108] (5) Add 0.15 g (active ingredient) of NRS-1230 emulsifier, 4 g of water, 1 g of acrylic acid, 4 g of styrene, and 10 g of isooctyl acrylate into a pre-emulsification tank.
[0109] (6) Dissolve 0.075 g of APS in 50 g of water to prepare an initiator solution;
[0110] (7) simultaneously adding the mixed monomers in step (5) and the initiator aqueous solution in step (6) to the reaction kettle in step (1) for 3 hours and keeping warm for 2 hours. After the reaction is completed, add 10% sodium hydroxide aqueous solution to adjust the pH value of the solution to 7.5;
[0111] Comparative Example 2: Precipitation Polymerization
[0112] (1) Add 0.5 g PVA2488 and 500 g deionized water into a reactor, start stirring and heat to 50°C;
[0113] (2) 24.83 g of acrylic acid, 50 g of acrylonitrile, 25 g of acrylamide, and 0.17 g of 1,3-butanediol dimethacrylate were mixed;
[0114] (3) 0.5 g of APS was dissolved in 50 g of water, and 0.5 g of NaHSO3 was dissolved in 50 g of water to prepare an oxygen-reduction initiator solution;
[0115] (4) simultaneously adding the mixed monomer in step (2) and the aqueous initiator solution in step (3) to the reaction kettle in step (1) for 3 hours. After the addition is complete, the temperature is raised to 80° C. and kept for 2 hours. A 10% aqueous sodium hydroxide solution is added to adjust the pH of the solution to 7.0.
[0116] Comparative Example 3: Emulsion Polymerization
[0117] (1) 0.5 g PVA2488, 0.5 g (active ingredient) NRS-1230 emulsifier, and 30 g deionized water were added to a pre-emulsification tank, and 14 g styrene, 25 g acrylic acid, 20 g acrylonitrile, 10 g acrylamide, 1 g 1,3-butanediol dimethacrylate,
[0118] 30 g of butyl acrylate was added to the pre-emulsification tank to prepare a pre-emulsion.
[0119] (2) Dissolve 0.5 g of APS in 50 g of water to prepare an initiator solution.
[0120] (3) adding 300 g of water into a reaction kettle, raising the temperature to 80 degrees Celsius, and simultaneously dripping the mixed monomers in step (1) and the initiator aqueous solution in step (2) into the reaction kettle in step (3) for 3 hours, keeping the temperature for 2 hours, and after the reaction is completed, adding 10% sodium hydroxide aqueous solution to adjust the solution pH to 7.5;
[0121] Comparative Example 4
[0122] Commercially available SBR3001A / BCQ15-2CMC binder system.
[0123] Comparative Example 5
[0124] Commercially available Indile LA136D PAA binder
[0125] The water-soluble binder for lithium-ion batteries prepared in Examples 1 to 5 of the present invention and the binder in Comparative Examples 1 to 4 are respectively mixed and dispersed with graphite, conductive carbon black and CMC dispersant to prepare lithium-ion negative electrode plates.
[0126] The specific preparation method is:
[0127] Preparation of negative electrode sheet slurry: Graphite negative electrode material, conductive carbon black, water-soluble binder for lithium ion battery of the present invention and comparative example (in terms of solid content) were mixed at a mass fraction of 96.5wt%, 1.0wt%, and 2.5w%, and deionized water was added at a total solid content of 45wt% to prepare negative electrode sheet slurry. After the uniformly dispersed slurry was passed through a 100-mesh sieve, it was coated on a 10μm thick copper foil as a current collector, and directly placed in a 120°C drying for 5 minutes, and then naturally cooled to room temperature in a furnace, and 10×10 4 The electrode sheet is obtained by rolling with a unit length load of N / m and used as the negative electrode of the lithium-ion battery.
[0128] The dissolution of polymer films was determined using the following method:
[0129] 30g of glue solution was placed in a 15cm×10cm×2cm container, placed in a 50℃ oven for 48h, the glue film was cut into 2cm×2cm square films, weighed and recorded as M1, placed in a covered glass sealed bottle filled with dimethyl carbonate DMC electrolyte, kept at 60℃ for 48h, and the electrolyte on the membrane surface was gently sucked off in a drying room and weighed and recorded as M2. The dissolution of the glue film is:
[0130] Dissolution = (M2-M1) / M1×100%, test results are shown in Table 3;
[0131] The negative electrode peel strength is determined by the following method:
[0132] The electrode sheets of the embodiment and the comparative example were cut into strips of 20 cm × 2.5 cm, and a 1 mm thick steel plate was adhered with double-sided tape on the current collector side, and a transparent tape was pasted on the coating layer side. The strips were peeled off in the 180° direction at a speed of 100 mm / min using a tensile testing machine, and the peeling stress was measured. The test results are shown in Table 3.
[0133] The flexibility of the negative electrode sheet is evaluated by the following method:
[0134] A core rod with a diameter of Φ=2.0 mm was placed on the current collector side of the rolled pole piece of the embodiment and the comparative example, and a bending test was performed. The state of the pole piece at this time was observed through an optical microscope. The intact pole piece was marked as ○, and the pole piece that fell off or cracked was marked as ×. The test results are shown in Table 3.
[0135] The graphite negative electrode material electrode sheet made of the water-soluble binder for lithium-ion batteries of the present invention is combined with a conventional positive electrode sheet, an electrolyte, and a separator to make a lithium-ion battery. The positive electrode main material is LG Chemical NCM811, the negative electrode main material is BYD SFC-R, the separator is Liyou New Energy P25 separator, and the electrolyte is Wanhua WT325.
[0136] Lithium-ion battery performance evaluation:
[0137] The lithium-ion battery was tested for its initial coulombic efficiency of the charge and discharge cycle and the capacity retention rate after 50 cycles by the constant current method. After 50 charge and discharge cycles, in the lithium-embedded state of the electrode plate, the ratio of the increase in the electrode plate thickness to the electrode plate thickness before charge and discharge was recorded as the electrode plate expansion rate (%). The results are shown in Table 3.
[0138] Table 3 Application performance evaluation results
[0139]
[0140]
[0141] It can be seen from Table 3 that the binders prepared by Examples 1 to 6 of the present invention have the characteristics of low polymer dissolution, high peel strength, good electrode flexibility, excellent cycle performance, and low electrode expansion rate compared with the binders prepared by Comparative Examples 1 to 5.
Claims
1. A water-based binder, the binder being obtained by polymerizing a raw material comprising the following components: a) 20 wt% to 45 wt% of at least one of an ethylenically unsaturated carboxylic acid or an ethylenically unsaturated carboxylic anhydride; b) 20 wt% to 45 wt% of an ethylenically unsaturated nitrile monomer; c) 5 wt% to 30 wt% of an ethylenically unsaturated hydrophilic monomer not containing a carboxyl group; d) 10 wt% to 40 wt% of ethylenically unsaturated hydrophobic monomers; e) 0.15 wt% to 1 wt% of a cross-linking monomer.
2. The aqueous adhesive according to claim 1, characterized in that The ethylenically unsaturated carboxylic acid and the ethylenically unsaturated carboxylic acid anhydride are preferably ethylenically unsaturated carboxylic acids, more preferably at least one of acrylic acid and methacrylic acid; and / or the ethylenically unsaturated nitrile monomer is selected from at least one of acrylonitrile, α-haloacrylonitrile, and α-alkylacrylonitrile, preferably at least one of acrylonitrile, α-chloroacrylonitrile, α-bromoacrylonitrile, methacrylonitrile, and ethacrylonitrile; and / or the carboxyl-free ethylenically unsaturated hydrophilic monomer is at least one of acrylamide, methacrylamide, hydroxyethyl acrylate, ethoxyethoxyethyl acrylate, hydroxyethyl methacrylate, sodium vinyl sulfonate, and sodium p-styrene sulfonate.
3. The aqueous adhesive according to claim 1 or 2, characterized in that: The ethylenically unsaturated hydrophobic monomer is styrene, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, hexyl acrylate, hexyl methacrylate, isooctyl acrylate, At least one of isooctyl methacrylate, decyl acrylate, decyl methacrylate, glycidyl acrylate, and glycidyl methacrylate; and / or the crosslinking monomer is at least one of diacetone acrylamide, ethyl acetoethoxy methacrylate, divinylbenzene, ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,6-hexanediol diacrylate, allyl methacrylate, and pentaerythritol triallyl ether.
4. The method for preparing the aqueous binder according to any one of claims 1 to 3, characterized in that: The steps include: Step 1: placing an aqueous solution of protective glue in a reactor and heating it; Step 2: Add the four monomers (a), (b), (c), (e) and an initiator into a reaction kettle to initiate a polymerization reaction; Step 3: After the polymerization is completed and the temperature is kept high, a neutralizing agent is added to adjust the pH to obtain a polymer solution A; Step 4: adding the emulsifier, (a), (d), (e) and the initiator into the reactor of step 3 simultaneously to further initiate the polymerization reaction; Step 5: After the polymerization is completed and the temperature is kept high, a neutralizing agent is added to adjust the pH to obtain a water-based adhesive.
5. The preparation method according to claim 4, characterized in that: In step 1, the protective colloid is selected from polyvinyl alcohol and / or sodium carboxymethyl cellulose; and / or, the amount of the protective colloid is 0.1-1wt%, preferably 0.3-0.8wt% of the total amount of the five monomers (a), (b), (c), (d), and (e); and / or, the heating temperature in step 1 is 30-85°C, preferably 35-80°C.
6. The preparation method according to claim 4 or 5, characterized in that: In the step 2, the initiator comprises an oxidant and a reductant, and the mass ratio of the oxidant to the reductant is 1:2-2:1, preferably 1:1-2:1; preferably, the oxidant is selected from at least one of ammonium persulfate, sodium persulfate, potassium persulfate, tert-butyl hydroperoxide, and hydrogen peroxide, preferably sodium persulfate; the reductant is selected from at least one of hydrosulfite, isoascorbic acid, sodium pyrosulfite, and sodium bisulfite, preferably sodium bisulfite; and / or, the amount of the oxidant is 0.1-1wt% of the total amount of the five monomers (a), (b), (c), (d), and (e), preferably 0.2-0.8wt%; the amount of the reductant is 0.1-1wt% of the total amount of the five monomers (a), (b), (c), (d), and (e), preferably 0.2-0.8wt%.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The temperature of the polymerization reaction in step 2 is 30-85°C. Preferably, the temperature is 35-80°C; the reaction time is 3-6h, preferably 4-5h; and / or, the insulation time in step 3 is 1-3h, Preferably, it is 1.5-2h; and / or, the emulsifier in step 4 is selected from one or more of sodium allyl alkyl succinate sulfonate, methacrylate polyether phosphate, allyl alkyl alcohol ether sulfate, double bond-containing alkyl alcohol ether sulfate, double bond-containing dialkyl sulfosuccinate, alkyl propylene phenoxy polyether sulfate, double bond-containing polyether ammonium phosphate, polyphenyl ring polyoxyethylene ether sulfate or sulfonate, and fatty alcohol polyoxyethylene ether sulfate; and / or, the amount of the emulsifier is 0.05-0.5wt% of the total amount of the five monomers (a), (b), (c), (d), and (e), preferably 0.1-0.3wt%.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In step 4, the initiator is selected from at least one of ammonium persulfate, sodium persulfate, potassium persulfate, tert-butyl hydroperoxide, and hydrogen peroxide, and the amount of the initiator is (a), (b), (c), (d), (e) 0.05-0.5wt% of the total amount of the five monomers, preferably 0.1-0.3wt%; and / or, in step 4 (a) The amounts of (a) and (e) monomers account for 2%-25% and 60%-97% of the total amount, respectively.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The reaction temperature in step 4 is 70-90°C, preferably 75-85°C; the reaction time is 3-6h, preferably 4-5h; and / or, the insulation time in step 5 is 1-3h, preferably 1.5-2h; and / or, the neutralizing agent in step 5 is selected from one or more aqueous solutions of NaOH, Na2CO3, LiOH, and lithium carbonate, and the adjusted pH is 6-8.
10. Use of the aqueous binder according to any one of claims 1 to 3 or the aqueous binder prepared by the preparation method according to any one of claims 4 to 9 as a binder for negative electrode active materials, wherein the negative electrode material is selected from artificial graphite, natural graphite, hard carbon, and silicon carbon.
Citation Information
Patent Citations
Water-soluble binders for lithium-ion batteries and their preparation methods, electrode sheets and batteries
CN111139002B
Three-dimensional cross-linked aqueous polymer binder as well as preparation method and application thereof
CN115312779A
Aqueous emulsion composition, and emulsion resin prepared by using same and use thereof
CN102140149A
Water-based binder for ceramic diaphragm of lithium ion battery
CN109609064A
Water-soluble binder for lithium ion battery and preparation method of water-soluble binder
CN111082062A
Cited By
Water-based negative electrode binder as well as preparation method and application thereof
CN121343516A
Water-based negative electrode binder as well as preparation method and application thereof
CN122474627A